2021
DOI: 10.1590/1983-1447.2021.20200403
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with anxiety, depression and stress in a COVID-19 nursing team

Abstract: Objective To investigate the levels of anxiety, depression and stress and their associated factors, among nursing professionals who make up the team working against COVID-19 of a University Hospital in the south of Brazil. Method Exploratory, descriptive, cross-sectional study conducted from May to July 2020. Results From the total number of professionals, 53.8% had anxiety; 38.4% depression; and 40.3%, stress. Age, length of service in the profession, job satisfaction and work shift showed a statistically s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 11 publications
(17 reference statements)
1
13
1
7
Order By: Relevance
“…The nursing professionals of a COVID-19 team have significant levels of anxiety, depression and stress, and the factors associated with depression and stress were identified [24]. According to the study by Appel et al, the nursing professionals of the COVID-19 team studied had significant levels of anxiety, depression and stress, and the factors associated with depression and stress were identified [25].…”
Section: Discussionmentioning
confidence: 99%
“…The nursing professionals of a COVID-19 team have significant levels of anxiety, depression and stress, and the factors associated with depression and stress were identified [24]. According to the study by Appel et al, the nursing professionals of the COVID-19 team studied had significant levels of anxiety, depression and stress, and the factors associated with depression and stress were identified [25].…”
Section: Discussionmentioning
confidence: 99%
“…21 Correspondingly, high depression, anxiety, and stress were also reported in nurses from Brazil and the authors highlighted the units in which nurses were working and less experience as important factors in developing depression, anxiety and stress. 22 Shifting our concerns to the evidence reported from Pakistan, there is a scarcity of published literature that is too reported from the metropolitan cities. A study from three major cities of Pakistan reported that depression, anxiety, and stress were frequent among nurses.…”
Section: Introductionmentioning
confidence: 98%
“…Já uma equipe de enfermagem atuante a nível hospitalar apresentou 53,8% dos profissionais com ansiedade, 38,4% com depressão e 40,3% com estresse, sendo este associado ao tempo de serviço, contrato de trabalho e satisfação no trabalho 31 . Outro estudo com profissionais de enfermagem revelou uma prevalência do estresse ocupacional de 90,6%, com associação ao maior nível de escolaridade, renda e nível de cuidado 32 .…”
Section: Resultsunclassified